Case report: Sclerosed hemangioma of the liver: A diagnostic challenge - Poras, M.; Katsanos, G.; Agrafiotis, A. C.; Demetter, P.; Pezzullo, M.; Lucidi, V. (Frontiers in Surgery, 2022)
Hemangiomas are the most common noncystic benign hepatic tumors and are usually incidentally discovered during routine radiological examinations. The diagnosis of hepatic hemangiomas with a typical presentation is generally easy with plain and cross-sectional imaging; however, it can be complicated when hemangiomas undergo histological changes such as fibrosis. Sclerosed hepatic hemangioma (SHH) is the extreme presentation of this fibrotic process. These atypical lesions can be misdiagnosed as primary hepatic malignancies or metastasis. Their diagnosis is established by histological examination. We report the case of a patient with an SHH, which was misdiagnosed as an intrahepatic cholangiocarcinoma. This article's aim is to draw attention to this infrequent pathology and underline the features of this benign tumor that could suggest its diagnosis prior to surgery to avoid unnecessary hepatic resections.